A simple and cost-effective transformation system for Porphyromonas gingivalis via natural competence - Abe, Kimihiro; Yahara, Hiroko; Nakao, Ryoma; Yamaguchi, Takehiro; Akeda, Yukihiro (Frontiers in Microbiology, 2024)
Porphyromonas gingivalis is a major oral bacterial pathogen responsible for severe periodontal diseases. Numerous studies have used genetic approaches to elucidate the molecular mechanisms underlying its pathogenicity. Typically, electroporation and conjugation are utilized for mutagenesis of P. gingivalis; however, these techniques require specialized equipment such as high-voltage electroporators, conjugative plasmids and donor strains. In this study, we present a simple, cost-effective transformation method for P. gingivalis without any special equipment by exploiting its natural DNA competence.P. gingivalis ATCC 33277 was grown to the early-exponential phase and mixed with a donor DNA cassette. This mixture was then spotted onto a BHI-HM blood-agar plate and incubated for one day to promote colony biofilm formation. The resulting colony biofilm was suspended in a liquid medium and spread onto antibiotic-containing agar plates.Transformants appeared within 4 to 5 days, achieving a maximum efficiency of 7.710 6 CFU/g. Although we optimized the transformation conditions using a representative strain ATCC 33277, but the method was also effective for other P. gingivalis strains, W83 and TDC60. Additionally, we discovered that deletion of PGN_0421 or PGN_0519, encoding putative ComEA and ComEC, abolished competency, indicating that these gene products are essential for the natural competence.